Finite Element Analysis for Bobbin Tool Friction Stir Welding - X.M. Liu; J.S. Yao; Z.D. Zou; Y. Cai; H. Meng (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
With DEFORM-3D finite element software, by thermo-mechanical coupling method, the physical modle for bobbin tool friction stir welding was set up. By this model, the temperature field and flow field of AA 2014 aluminium alloy work plate of 6mm was analyzed, which provides useful information for the investigation of this new process. Simulation results show that the temperature field of the cross section presents symmetry approximately about the mid thickness of the work plate. The high temperature zone has large radius at bottom and top surfaces near the shoulders while small radius at the mid thickness, like a waist, which is verified by the experiments. The relativey highest steady temperature keeps about 360℃. Groove defects are easy to be found in the simulation.